Separation anxiety of personality: methodological research dimension - Гайдучик, Петро Данилович (Psychological Counseling and Psychotherapy, 1970)
The review of separation anxiety of a personality problem actualizes its theoretical and methodological specification in the structure of general psychological knowledge and applied psychotherapeutical aspects of acquiring psychological security. The construct of separation anxiety is considered and its types, forms and function displays are concretized. It is pointed out that the content and dynamics of separation influence depend both on the personal resources of emotional security acquisition and the system of psychotherapeutic methods that contribute to personal responsibility and maturity.